The Sharia Funding Risk Issues in Fintech Securities Crowdfunding: Realization of Legal Certainty in the Shari'ah Perspective - Alhadiansyah, Alhadiansyah; Djun'astuti, Erni; Susila, Sugeng; Marnita, Marnita; Aprilsesa, Tri Dian (SASI, 2023)
Introduction: In the era of globalization and information technology, fintech is transforming the financial sector, including fintech securities crowdfunding, which is a funding model based on the participation of many small investors. In the context of sharia, sharia principles regulate financial transactions and services, while crowdfunding fintech securities is a popular phenomenon in sharia funding, but requires investor protection regarding investment risk and legal protection.Purposes of the Research: To analyze the legal certainty of protection for investors who invest in Islamic funding through fintech securities crowdfunding in Indonesia and analyze the risks faced by investors in this context.Methods of the Research: This study uses qualitative normative legal research methods to understand legal certainty and investor protection in Islamic funding through Fintech Securities Crowdfunding. Data collection was carried out through literature study and then analyzed qualitatively to identify patterns, themes and related issues.Results of the Research: Sharia funding through Fintech Securities Crowdfunding in Indonesia provides attractive Islamic investment opportunities but also involves various risks such as business risk, liquidity, legal, sharia, and others. Legal certainty regulated by Financial Services Authorityand Sharia Supervisory Board is the key in providing protection to investors. OJK regulations ensure information transparency and compliance with sharia principles, so that investors can invest with confidence according to sharia values. Thus, an investment ecosystem that has integrity and is inclusive within the sharia framework can be realized.